Advanced Finite Element Simulation with MSC Marc Application of User Subroutines - Javanbakht, Zia.; Öchsner, Andreas; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book offers an in-depth insight into the general-purpose finite element program MSC Marc, which is distributed by MSC Software Corporation. It is a specialized program for nonlinear problems (implicit solver) which is common in academia and industry. The primary goal of this book is to provide a comprehensive introduction to a special feature of this software: the user can write user-subroutines in the programming language Fortran, which is the language of all classical finite element packages. This subroutine feature allows the user to replace certain modules of the core code and to implement new features such as constitutive laws or new elements. Thus, the functionality of commercial codes ('black box') can easily be extended by linking user written code to the main core of the program. This feature allows to take advantage of a commercial software package with the flexibility of a 'semi-open' code. .
Fortran - Advanced Features -- Introduction to Marc/Mentat -- Basic Examples -- Advanced Examples -- A Listing of the Customized Modules.
Keywords: Mechanics, Applied; Solids; Numerical analysis; Computer-aided engineering; Compilers (Computer programs).; Solid Mechanics; Numerical Analysis; Computer-Aided Engineering (CAD, CAE) and Design; Compilers and Interpreters